Analysis of Case 1 from the 5th High Lift Prediction Workshop for multiple angles of attack using ANSYS Fluent (2025)
This document is a continuation of the work “Analysis of Case 1 of the 5th High Lift Prediction Workshop with Ansys Fluent” and presents the use of the ANSYS Fluent software to estimate the drag, lift, and pitching moment coefficients for different angles of attack for the High Lift Common Research Model Wing Body (CRM-HL-WB) geometry of Test Case #1 of the Fifth High Lift Prediction Workshop (HLPW-5) of the American Institute of Aeronautics and Astronautics and the National Aeronautics and Space Administration.